Epidemiology of acute respiratory infections in children - preliminary results of a cohort in a rural north Indian community. Issue 1 (December 2015) - Krishnan, Anand; Amarchand, Ritvik; Gupta, Vivek; Lafond, Kathryn; Suliankatchi, Rizwan; Saha, Siddhartha; Rai, Sanjay; Misra, Puneet; Purakayastha, Debjani; Wahi, Abhishek; Sreenivas, Vishnubhatla; Kapil, Arti; et al.
Abstract Background Despite acute respiratory infections being a major cause of death among children in developing countries including India, there is a lack of community-based studies that document its burden and aetiology. Methods A dynamic cohort of children aged 0–10 years was established in four villages in a north Indian state of Haryana from August 2012 onwards. Trained health workers conducted weekly home visits to screen children for acute respiratory infection (ARI) defined as one of the following: cough, sore throat, nasal congestion, earache/discharge, or breathing difficulty. Nurses clinically assessed these children to grade disease severity based on standard age-specific guidelines into acute upper or lower respiratory infection (AURI or ALRI) and collected nasal/throat swabs for pathogen testing. Results Our first year results show that ARI incidence in 0–10 years of age was 5.9 (5.8–6.0) per child-year with minimal gender difference, the ALRI incidence in the under-five age group was higher among boys (0.43; 0.39–0.49) as compared to girls (0.31; 0.26–0.35) per child year. Boys had 2.4 times higher ARI-related hospitalization rate as compared to girls. Conclusion ARI impose a significant burden on the children of this cohort. This study platform aims to provide better evidence for prevention and control of pneumonia in developing countries.